Inverted hysteresis as a diagnostic tool for perovskite solar cells: Insights from the drift-diffusion model - Clarke, Will; Cowley, Matthew V.; Wolf, Matthew J.; Cameron, Petra; Walker, Alison; Richardson, Giles (Journal of applied physics, 2023)
Despite current–voltage hysteresis in perovskite solar cells (PSCs) having been the subject of significant research over the past decade, inverted hysteresis (IH), although frequently observed, is still not properly understood. Several mechanisms, based on numerical simulations, have been proposed to explain it but a satisfactory description of the underlying cause remains elusive. To rectify this omission, we analyze a drift-diffusion model of a planar three-layer PSC, using asymptotic techniques, to show how inverted hysteresis comes about. The asymptotic analysis of the drift-diffusion model yields a simple approximate model that shows excellent agreement with numerical simulations of the full drift-diffusion model provides fundamental insights into the causes of IH and reconciles the alternative explanations found in the literature. This approximate model is analyzed further to isolate the material properties and external conditions that contribute to inverted hysteresis and constitutes a diagnostic tool in which the appearance of IH can be used to infer properties of the cell.